RETRACTED: Nexus Between Consumer’s Motivations and Online Purchase Intentions of Fashion Products: A Perspective of Social Media Marketing - Yu, Feng; Wenhao, Qian; Jinghong, Zhou (Frontiers in Psychology, 2022)
This study aimed to investigate the effects of customers' motivations (specifically young consumers) on online purchase intentions as mediated by commitment towards online fashion retailers. The survey method was used to collect data from Chinese respondents using a questionnaire. The convenience sampling technique was used to collect data from two hundred and seventy-five respondents. Collected data was analyzed on smart-PLS using the structural equation modeling technique. Results of the study show a significant and positive impact of social empowerment and remuneration motivations on consumer commitment online purchase intention. Further results show that consumer commitment partially mediates the relationship between social empowerment, remuneration, and online purchase intention. This study contributes to the literature in the domain of consumer commitment by focusing on the underlying needs and motivations of consumers. The researchers have demonstrated a strong need to understand the dynamics of commitment due to its importance in affecting purchase intention. This study also has several implications that guide online retailers how to motivate consumers with social, remuneration and empowerment incentives to develop their intention to purchase online. Fashion retailers are suggested to gratify certain consumer motives to increase commitment. Specifically, among the three motives, empowerment motivation emerged as the strongest predictor of consumer commitment in social media environment. Using uses and gratification theory and theory of reasoned action this the first novel study that empirically discussed the dimensions of consumer motivation, consumer commitment and specifically young consumers intention to purchase fashion products online.